Constraint on the Higgs-Dilaton Potential via Warm Inflation in Two-Time Physics - Vo Quoc Phong; Ngo Phuc Duc Loc (Advances in High Energy Physics)
Within the SP2,R symmetry, the two-time model (2T model) has six dimensions with two dimensions of time and the dilaton field that can be identified as inflaton in a warm inflation scenario with potential of the form ~ϕ4. From that consideration, we derive the range of parameters for the Higgs-Dilaton potential, the coupling constant between Higgs and Dilaton (α) is larger than 0.0053 and the mass of Dilaton is smaller than 10−7 GeV. Therefore, the 2T model indirectly suggests that extra dimension can also be a source of inflation.